Progressive collapse resistance of reinforced concrete structures - Du Panwei (2016)
Structures under abnormal loading condition, such as fire, blast and natural disaster may experience local failure of a primary structural component, which may lead to collapse of the whole structure. Alternative Load Path (ALP) method is an effective way to evaluate the progressive collapse resistance by removing one middle column. Experimental programmes comprising corner column removal scenario and exterior column removal scenario for both 3-D RC-frames and RC beam-slab substructures were carried out to study the structural behaviour and explore the internal mechanisms. In 3-D RC-frame tests, with the increase of middle joint displacement, different structural mechanisms, e.g. Flexural Action (FA), Compressive Arch Action (CAA) and CaTenary Action (CTA) were mobilized in sequence. The development of CTA significantly enhanced the structural capacity, by utilizing the reserved strength of top reinforcement. However, sufficient horizontal restraints and ductility were required for the formation of CAA and CTA. In RC beam-slab substructures, Tensile Membrane Action (TMA) as one of the ALPs was developed in slab. TMA consisted of the tensile membrane in central zone and a compressive ring in peripheral region. Similar to CTA, TMA also helped to increase the structural resistance beyond the flexural capacity. Preliminary structural analysis which encompassed plastic theory, yield line theory and computer aided analysis was applied to each specimen. The plastic hinge locations, yield line patterns and the corresponding flexural capacities were calculated and validated with the test results. These analyses denoted good agreements with the experimental results, and this method may be used to calculate the flexural capacity for structures with different kinds of design. Future work was also recommended for this research topic to obtain a more realistic and comprehensive study. It is recommended to include the investigation of analytical models for CTA and TMA, and the conduct of dynamic tests and multi-storey tests.